Nutrition Standards For Infants and Young Children can be Implemented by Family Child Care Home Providers - Lorrene D. Ritchie PhD,RD; Victoria Keeton RN,MS,PNP; Danielle L. Lee MPH,RD; Klara Gurzo MA; Elyse Homel Vitale MPH; Lauren E. Au PhD,RD; Abbey Alkon PhD,RN,CPNP (Global Pediatric Health, 2021)
The study evaluated an educational intervention with family child care home (FCCH) providers to implement nutrition standards. A convenience sample of licensed California FCCH providers (n = 30) attended a 2-hour, in-person group training in English or Spanish on nutrition standards for infants and children aged 1 to 5 years. Provider surveys and researcher observations during meals/snacks were conducted pre- and 3 months post-intervention. Providers rated the training as excellent (average score of 4.9 on a scale of 1-5). Adherence, assessed by survey and observation and compared over time using paired t -tests, increased from an average of 36% pre-intervention to 44% post-intervention ( P  = .06) of providers (n = 12) for infant standards and from 59% to 68% ( P  < .001) of providers (n = 30) for child standards. One-third (39%) of providers rated infant standards and 19% of providers rated child standards as difficult to implement. Nutrition standards can be implemented by FCCH providers after an educational intervention; a larger study is warranted with a representative group of providers.